Desempenho de leitões na maternidade submetidos a diferentes fontes de aquecimento - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The biggest challenge in pig farming is to provide thermal comfort for sows and piglets, which are in the same environment. The thermal comfort zone for sows is 10 to 15 ºC and for piglets is 30 to 32 ºC, being gradually reduced over the weeks. So that sows and piglets stay in the same environment, a creeper is used with the aid of a heat source, in this way it is possible to control the temperature and offer an environment with artificial heating for the litter. The aim of this project was to evaluate different sources of heating for piglets in the farrowing pen. The experiment was carried out in a pig farm, in Planaltina, Goiás, Brazil. Three lots were evaluated simultaneously in the maternity, housing ten piglets for each lot, with DB 90 genetic piglets, with five replications. The creeper 1 was heated with an infrared lamp 250w 220v-1, the creeper 2 was heated with an incandescent lamp of 150w 220v-1 and the creeper 3 was heated with an infrared/incandescent lamp of 220w 220v-1. He evaluated the relative humidity of the air, ambient or dry bulb temperature, wet bulb temperature, dew point temperature, black globe temperature and creeper temperature using Thermal Stress Meter (IBUTG) AK 887® equipment. Physiological parameters such as respiratory rate and skin surface temperature (nape, shoulder and leg) were also evaluated using a digital laser thermometer and behavior through visual observations. Data were evaluated through analysis of variance, adopting the F test and Tukey's test, at a 5% probability level. Initial weight, final weight, daily weight gain, UTI and temperature did not show statistical differences. The ITGU showed statistical differences, demonstrating the highest value for the heat source with an infrared lamp. The UR, on the other hand, presented statistical differences. For the evaluated physiological parameters of body surface temperature observed values for neck and shoulder with statistical differences between treatments, and for leg there were no differences. The FR also showed statistical differences between the heat sources. Finally, the frequency of behaviors there were no statistical differences only in the behaviors of drinking water and moving outside the creeper, and the others showed statistical differences. It can be concluded that the microclimate generated by the heat sources coming from the lamps exceeded the range of thermal comfort that is required for piglets.
Performance of piglets in the maternity ward subjected to different heating sources
Keywords: Ambiência; Bem-estar animal; Suinocultura; Temperatura; Produção animal; Ambience; Animal welfare; Swine farming; Temperature; Animal production; CIENCIAS AGRARIAS